ANALISIS RESPON PENAWARAN DAN PERMINTAAN KARET ALAM INDONESIA DI PASAR DUNIA - Agrippina Sinclair; Djaimi Bakce; Jum'atri Yusri (Indonesian Journal of Agricultural Economics, 2017)
Indonesia is the largest natural rubber producer in the world after Thailand. Indonesia was ranked second in the world in terms of production, and ranked first in terms of land area. Beside Thailand, the main competitor of indonesia’s natural rubber in the international market comes from Malaysia. Observing that it carried out a study with the aim to analyze the response of supply and demand for Indonesia’s natural rubber in the international market. This study uses econometric approach, simultaneous equation model, using two stages least square method. The main results of this study indicate that the supply and demand for Indonesia natural rubber. Thailand is a country that is decisive in the formation of the world’s natural rubber prices from the supply side. This is closely related to the Thai government that consistently develop natural rubber from the upstream to the downstream. In Indonesia, there is the impression the government’s attention is diverted to the development of palm oil. Thus, to develop natural rubber in Indonesia is required to stabilize natural rubber prices through increased raw material quality of natural rubber both at the level of people’s plantations and large estates. In addition, the downstream industrial policy, particularly natural rubber processing industry, which had been launched a few years ago, needs to be consistently implemented by the Indonesia  government.